Influence of nanoparticle morphology and its dispersion ability regarding thermal properties of water used as phase change material. (5th January 2018) - Barreneche, Camila; Mondragon, Rosa; Ventura-Espinosa, David; Mata, Jose; Cabeza, Luisa F.; Fernández, A. Inés; Enrique Julia, J.
Highlights: Addition of carbon nanoparticles to water used as phase change material. Reduction of subcooling degree and increase of thermal conductivity. Influence of nanoparticle morphology: use of spheres, nanotubes and nanosheets. Abstract: Nanoparticles with different morphologies were added to water to study if the morphology of the nanoparticles affects the main parameters of water used as phase change material (PCM). Considered morphologies were spherical, tubes and sheets in the form of spherical carbon black nanoparticles (CB), multiwalled carbon nanotubes (MWCNT), and graphene oxide nanosheets (GO). Results demonstrate that effectively the morphology of nanoparticles affect the thermophysical properties of the nano-enhanced PCM (NePCM). Depending on the morphology of the added nanoparticle, the final NePCM will have different subcooling and thermal conductivity, whereas its phase change enthalpy is not affected and, therefore, is the same for all produced NePCM.